THEORETICAL RESEARCH OF SOCIAL ENTREPRENEURSHIP IN THE REGION (ON THE EXAMPLE OF THE ATYRAU REGION) - M.K. Baymuhasheva,; R.K. Sabirovа, (Academic Journal of Physical and Chemical Sciences, 2019)
The main difference, according to the authors, lies not in the plane of motivation (to do it for the sake of money or from altruism), but in the sphere of the characteristics of “anticipated and produced value” (good). In the case of ordinary business, the market value becomes a blessing, which can be expressed in the category of income and profit (which is misleading when comparing the motivation of the two types of entrepreneurs). In the case of social entrepreneurship, it is the value expressed in the advantage that a significant part of society or society as a whole receives from the “large-scale transformation” produced by the social entrepreneur. At the same time, the target groups for which “value” is intended are the least protected and least prosperous segments of the population, who do not have either financial resources or political levers to achieve “the value obtained as a result of transformation” by their own efforts.